UMPSA honours outstanding lecturers at the Cendekia Bitara Awards - Naqiah, Puaad (UMPSA, 2024)
KUANTAN, 28 September 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) celebrated its outstanding lecturers at the Cendekia Bitara Awards (ACB) ceremony, held at the Grand Darul Makmur Hotel in Kuantan.